Isolation and properties of beta-glucosidase from Ruminococcus albus. - Ohmiya, K (1985)
An enzyme active against p-nitrophenyl-beta-D-glucoside was purified from logarithmic-phase cells of Ruminococcus albus cultivated in a medium containing ball-milled cellulose. The purification yielded homogeneous enzyme after an approximately 520-fold increase in specific activity and a 9% yield. The enzyme was identified as a beta-glucosidase because it can hydrolyze cellobiose and cellooligosaccharides to glucose from the nonreducing ends.